The Effect of Oil Price Fluctuation on the Economy of Nigeria - Gylych, Jelilov; Jbrin, Abdullahi Ahmad; Celik, Bilal; Isik, Abdurrahman (International Journal of Energy Economics and Policy, 2020)
The aim of the study is to find the empirical analyses of the impact of oil price fluctuation on the monetary instrument in Nigeria, by looking at their relationships. Specifically, we analyzed the role of Exchange rate, Inflation, Interest rate and how they respond to shocks in oil price. We explored the frequently used Toda–Yamamoto model (TY), by adopting the TY Modified Wald (MWALD) test approach to causality, Forecast Error Variance Decomposition (FEVD) and Impulse Response Functions (IRFs). The study covered the period Q1 1995 to Q4 2018, and our findings from MWALD test indicated that there is a uni-directional causality at 5% level of significance a response of lnintr due to positive change in lnoilpr and next, and the combination of variables with lnintr as a dependent variable contributed to it changes. This also corroborates with our findings in FEVD, of lnintr, contributing to its future error variation of 97.41%, 60.94% and 54.34% for the first, ninth and tenth year, and followed by lnoilpr, contributing 24.86% and 31.12% in the ninth and tenth year, also lnexcr contributes 10.35%, 10.80% and 10.19% in fourth, fifth and sixth year into the future, this indicates also a strong causal relationship into the future. The IRFs also complement our findings, where we observed that the relationship between lnoilpr independent variable and lnintr as the dependent variable is an inverse relationship, while other independent variables are positive. Keywords: Oil Price, Exchange rate, Inflation, Interest rate, Toda–Yamamoto. JEL Classifications: Q1, Q3, Q41, Q47 DOI: https://doi.org/10.32479/ijeep.9493